Immigration, Political Ideologies and the Polarization of American Politics - Axel Dreher; Sarah Langlotz; Johannes Matzat; Anna Maria Mayda; Christopher Parsons (Center for Economic Studies and Ifo Institute (CESifo), 2020)
We study the extent to which migrant inflows to the United States affect the political polarization of campaign donors and the ideology of politicians campaigning for the House of Representatives in the 1992-2016 period. Implementing various polarization measures based on ideology data derived from 16 million campaign finance contributors, our results show that migrant inflows causally increase the polarization of both campaign donations and leading political candidates. Our estimates hold over the medium-run, although the effects decline over time. The effects of migration are stronger if counties host migrants from more distant cultures, or if incoming migrants are similarly educated. Our main results hold when we focus on refugees as opposed to all immigrants on aggregate.
Keywords: J15; F52; F63; 330; migration; refugees; polarization; political ideology; United States